The Art and Literature Areativity, Kurdish Poets and Poems As An Example - Obaid, Arkhawan Mohammed (Journal of University of Raparin, 2021)
Abstract The art and literature creativity, Kurdish poets and poems as an example is the name of a theoretical and practical research. It is theoretical because in the first part it presents the principles and the regulations of the research for the first time. And it is practical because in the second and third parts of the the research is : Supported in a way of practicing the ideas in Kurdish pomes and the experiences of Kurdish poets, the situation of stopping creativity is a situation of repletion, fullness, giving up, satisfaction,missing creativity and initiative for creativity that happens to the producers person in which the producer is not able to produce new products or things. This repletion could be temporary or permanent. It has two types ( psychological and formational repletion) This research can be applied to all types of practical arts but in this research it is just practiced on Kurdish pomes only. This research is based on both the psychological and the formational terms. The research presents the important aims of the research , defining the terms, classifying the motivators of creativity and it is effects on the poets products.